Spectrophotometric Determination of Formation Constants of Iron(III) Complexes with Several Ligands - José J. N. Segoviano-Garfias; Gabriela A. Zanor; Fidel Ávila-Ramos; Egla Yareth Bivián-Castro; Carlos A. Rubio-Jiménez (Chemistry, 2022)
Dye-sensitized solar cells transform solar light into electricity. One commonly used dye is a ruthenium complex. However, the use of ruthenium has been shown to have several disadvantages. In this study, via singular spectrum analysis using HypSpec software, we determined the formation constants and calculated individual electronic spectra of species of iron(III) with several ligands (1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane, 2,2′-bipyridyl, 5,5-dimethyl-2,2′-bipyridyl, 4,4′-di-tert-butyl-2,2′-bipyridyl, 1,10-phenanthroline, and 3,4,7,8-tetramethyl-1,10-phenanthroline) in methanol solution. We present a spectral comparison of the complexes reported here to the ruthenium complex: tris-(2,2′-bipyridyl)ruthenium(II).